Pengembangan Model Pelatihan Kewirausahaan untuk Perempuan Pengangguran di Kabupaten Demak - Indriyatni, Lies; Purwanto, Agus Budi; Wahyuningsih, Panca (Jurnal Aplikasi Manajemen, 2015)
This Research aims to find entrepreneurship training model for unemploymentwomen in Demak regency. The Research model can be used as a reference for the implementationof the entrepreneurship training program in various formal and informal institutions.It is also useful for management entrepreneurship training program. The method uses in thisstudy follows the ten stages of R & D developed by Borg, et al. (2007). In this study, the tenstages modified into eight stages in order to adjust with the research context. The steps wereresearch and information collection and preliminary stages of testing in the field throughFocus Group Discussion (FGD). The implementation of entrepreneurship training uses problem-based learning (PBL) method. Based on data collected from all respondents, they hadfollowed training programs or entrepreneurial skills that comes from the state budget, butthey were not be able to create new entrepreneurs. This is due to the organizer programs didnot include supporting entrepreneurship in the curriculum program that they perform. Entrepreneurshiptraining models that developed in this research are covering: 1) system ofselection participants, 2) material and training method, 3) apprenticeship, 4) capital management,5) mentoring for business, 6) evaluation and report.